GIS mapping of basal stem rot disease in relation to soil series among oil palm smallholders - Kannan, Parthiban; Vanitah, R.; Jusoff, Kamaruzaman; A. A., Nordiana; A. R., Anuar; O., Wahid; A. B., Hamdan (Science Publications, 2016)
Basal Stem Rot (BSR) is a disease caused by fungus which affect oil palm tree. This study aims to visualize the geographical distribution of BSR incidence among oil palm smallholders in Selangor using Geographical Information System (GIS) and its relationship to the type of soil series. The geographical distribution of BSR incidence of smallholders in Selangor were mapped using 168 Global Positioning System (GPS) coordinate of possible infected area. The methodology followed in finding the relationship between BSR and soil series by assigning percentage of BSR incidence based on type of soil series. Majority of the BSR incidences were found to be confined to the Selangor-Kangkong (Aeric Tropic Fluvaquent-Typic sulfuric tropic fluvaquent) soil series followed on Peat (Typic Fibric Tropohemist) soil then Kranji (Typic Sulfaquents) soil series and finally the Briah-Organic Clay and Muck (Typic Tropic Fluvaquent) soil series. Distribution pattern of the BSR revealed that most of the incidences were confined along the coastal area which might be due to the planting of oil palm in previous coconut stands. Low pH of Selangor (Aeric Tropic Fluvaquent) and Peat (Typic Fibric Tropohemist) soil series shows a higher BSR incidence while high pH of Kranji (Typic Sulfaquents) and Briah (Typic Tropic Fluvaquent) soil series shows slightly lower BSR incidence. From this study, it can be concluded that the distribution of BSR were mostly confined to the coastal areas which might be due to the planting of oil palm in previous coconut stands rather than any relationship with the type of soil series. This distribution map of BSR incidence can be used to deliver effective extension services regarding BSR to smallholders with a specified target based on location and soil series.